IFNγ at the early stage induced after cryo-thermal therapy maintains CD4+ Th1-prone differentiation, leading to long-term antitumor immunity - Wang, Junjun; Lou, Yue; Wang, Shicheng; Zhang, Zelu; You, Jiaqi; Zhu, Yongxin; Yao, Yichen; Hao, Yuankai; Liu, Ping; Xu, Lisa X. (Frontiers in Immunology, 2024)
Introduction Recently, more and more research illustrated the importance of inducing CD4+ T helper type (Th)-1 dominant immunity for the success of tumor immunotherapy. Our prior studies revealed the crucial role of CD4+ Th1 cells in orchestrating systemic and durable antitumor immunity, which contributes to the satisfactory outcomes of the novel cryo-thermal therapy in the B16F10 tumor model. However, the mechanism for maintaining the cryo-thermal therapy-mediated durable CD4+ Th1-dominant response remains uncovered. Additionally, cryo-thermal-induced early-stage CD4+ Th1-dominant T cell response showed a correlation with the favorable prognosis in patients with colorectal cancer liver metastasis (CRCLM). We hypothesized that CD4+ Th1-dominant differentiation induced during the early stage post cryo-thermal therapy would affect the balance of CD4+ subsets at the late phase. Methods To understand the role of interferon (IFN)-γ, the major effector of Th1 subsets, in maintaining long-term CD4+ Th1-prone polarization, B16F10 melanoma model was established in this study and a monoclonal antibody was used at the early stage post cryo-thermal therapy for interferon (IFN)-γ signaling blockade, and the influence on the phenotypic and functional change of immune cells was evaluated. Results IFNγ at the early stage after cryo-thermal therapy maintained long-lasting CD4+ Th1-prone immunity by directly controlling Th17, Tfh, and Tregs polarization, leading to the hyperactivation of Myeloid-derived suppressor cells (MDSCs) represented by abundant interleukin (IL)-1β generation, and thereby further amplifying Th1 response. Discussion Our finding emphasized the key role of early-phase IFNγ abundance post cryo-thermal therapy, which could be a biomarker for better prognosis after cryo-thermal therapy.